Uma estratégia alternativa de financiamento - Botelho, César Queiroz (2016)
This study investigates an alternative financing scheme for individuals and firms whom have no interest in getting rid of its investments using the Brazilian stock market. It compares the payoff structure of this financing strategy with a traditional bank loan. It concludes that in this kind of operations, the possibility of paying less interest than banks are significant, mainly with the purchase of 50% calls over the financed.